Job-worker mismatch and cognitive decline - Andries de Grip; Hans Bosma; Dick Willems; Martin van Boxtel (Institute for the Study of Labor (IZA), 2007)
We have used longitudinal test data on various aspects of people's cognitive abilities to analyze whether overeducated workers are more vulnerable to a decline in their cognitive abilities, and undereducated workers are less vulnerable. We found that a job-worker mismatch induces a cognitive decline with respect to immediate and delayed recall abilities, cognitive flexibility and verbal fluency. Our findings indicate that, to some extent, it is the adjustment of the ability level of the overeducated and undereducated workers that adjusts initial job-worker mismatch. This adds to the relevance of preventing overeducation, and shows that being employed in a challenging job contributes to workers' cognitive resilience.
Keywords: 330; Überqualifikation; Kognition; Arbeitsmarkt; Matching; Qualifikation; Niederlande